The Influence of Digital Marketing and Influencer Marketing on Purchase Behavior Through Purchase Intention of Ozakazik.co Consumers on Shopee - Faozan Aditiya Pradana; Osly Usman (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study is theoretically grounded in examining how digital marketing and influencer marketing influence purchasing behavior, with purchase intention conceptualized as a mediating construct. Specifically, it investigates the structural relationships between these marketing stimuli and consumer decision making processes in the context of Ozakazik.co consumers on the Shopee platform. A quantitative research design was employed, involving 61 respondents who had previously purchased Ozakazik.co products, selected through a saturated sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among the variables. Results from the empirical study demonstrate that digital marketing exerts a statistically significant beneficial influence on purchasing behaviour (β = 0.269; p = 0.025) and purchase intention (β = 0.646; p < 0.001). In contrast, influencer marketing exhibits a notable direct impact on purchasing behaviour (β = 0.198; p = 0.028), although its influence on purchase intention is not statistically significant (β = 0.277; p = 0.084). Furthermore, buy intention strongly affects purchasing behaviour (β = 0.511; p < 0.001), affirming its position as a critical mediating variable within the model. Digital marketing and purchasing behaviour are substantially mediated by purchase intention, according to the mediation study (β = 0.330; p = 0.004). Even so, it is not a mediator in the relationship between influencer marketing and buying behaviour (β = 0.141; p = 0.116). According to the results, digital marketing affects the formation of buy intention and subsequent purchasing behaviour in a more consistently structured manner than influencer marketing does, according to the proposed conceptual framework. Cognitive purpose is a key mediating characteristic that the study identifies as theoretically significant for understanding how marketing cues translate into consumer behaviour.